2019
DOI: 10.2147/rrtm.s186723
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of intestinal parasites and its risk factors among food handlers in food services in Nekemte Town, West Oromia, Ethiopia</p>

Abstract: Background Food-borne diseases are a public-health problem in developed and developing countries. The World Health Organization (WHO) estimated that in developed countries, up to 30% of the population suffers from food borne diseases each year and more in developing countries, where up to 2 million deaths are estimated per years. Objective To assess the prevalence of intestinal parasites and its associated risk factors among food handlers in Nekemte town. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
29
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 14 publications
10
29
3
1
Order By: Relevance
“…The odds of not having handwashing after defecation were 2.71 times more likely to develop intestinal parasitic infections than their counterparts. This finding is supported by the studies conducted in Kenya [40], Gambia [41], Pakistan [42] and Ethiopia [30,43,44]. This might be due to feco-oral microorganism transmissions.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The odds of not having handwashing after defecation were 2.71 times more likely to develop intestinal parasitic infections than their counterparts. This finding is supported by the studies conducted in Kenya [40], Gambia [41], Pakistan [42] and Ethiopia [30,43,44]. This might be due to feco-oral microorganism transmissions.…”
Section: Discussionsupporting
confidence: 69%
“…The odds of untrimmed fingernail were 3.04 times more likely to acquire intestinal parasitic infections than their counterparts. This finding is supported by the studies conducted in Ethiopia [30,43,44]. This might be due to the fact that untrimmed fingernail may contain dust particles and microorganisms which facilitates in easily transmissions of microorganisms feco-orally.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This is consistent with the studies. [49][50][51][54][55][56][57] This might be due to contaminated hands and fingers can serve as a carrier for the transmission of intestinal parasitic infections. 50,56,[58][59][60] Conclusions Findings of the present study showed that the study area was heavily infected with protozoan infections, implying that they are continued major public health problems.…”
Section: Discussionmentioning
confidence: 99%
“…AD and BA developed the draft proposal under the supervision of GG and GD. All authors (AD, BA, GG Authors' Information 1 Department of Medical Laboratory Sciences, College of Health Sciences, Woldia University,…”
Section: Fundingmentioning
confidence: 99%